Tolerance in the Prohibition of Interfaith Marriage: A Normative Analysis of Islamic Law and Legal Regulations in Indonesia - Armayanto, Harda; Silmi, Nadaa Afifah (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2025)
This article aims to examine the scope of tolerance regarding the prohibition of interfaith marriage by integrating the perspectives of Islamic law and Indonesia’s positive legal system. The analysis focuses on the influence of Supreme Court Circular (SEMA) No. 2 of 2023 and Law No. 1 of 1974 on Marriage on marriage policy in Indonesia. The controversy surrounding interfaith marriage often centers on the tension between individual freedom, human rights, and the enforcement of religious norms as the foundation of the national legal system. This qualitative study employs a normative-juridical approach to interpret legal regulations in dialogue with Islamic scriptural texts (nash syar‘i). Data were collected through a literature review, analysis of legal regulations, and examination of religious fatwas that influence social practices. The findings indicate that the prohibition of marriage between Muslim women and non-Muslim men should not be perceived as a form of intolerance. Instead, it functions as a mechanism for protecting religious values and serves as a legal instrument to balance individual rights with social order in a pluralistic society. Consequently, this study asserts that restrictions on interfaith marriage do not inherently contradict the principle of tolerance. On the contrary, they may be interpreted as a form of tolerance rooted in legal and religious values that promote peaceful coexistence while safeguarding the integrity of religious teachings and social harmony.Abstrak: Artikel ini bertujuan mengkaji ruang toleransi dalam larangan perkawinan beda agama dengan memadukan perspektif hukum Islam dan hukum positif Indonesia. Fokus analisis diarahkan pada pengaruh Surat Edaran Mahkamah Agung (SEMA) No. 2 Tahun 2023 serta Undang‑Undang No. 1 Tahun 1974 tentang Perkawinan terhadap kebijakan perkawinan di Indonesia. Kontroversi pernikahan beda agama kerap berpusat pada tarik‑menarik antara kebebasan individu, hak asasi manusia, dan keberlakuan norma agama sebagai fondasi sistem hukum nasional. Penelitian dengan jenis kualitatif ini menggunakan pendekatan normatif‑yuridis untuk membaca secara dialogis teks regulasi dengan nash syar‘i. Data dikumpulkan melalui studi pustaka, telaah peraturan perundang‑undangan, dan fatwa keagamaan yang berpengaruh dalam praktik sosial. Hasil kajian menunjukkan bahwa larangan perkawinan antara perempuan Muslim dan laki‑laki non‑Muslim bukan merupakan bentuk intoleransi, melainkan mekanisme perlindungan nilai‑nilai agama serta instrumen hukum untuk menyeimbangkan hak individu dengan ketertiban sosial di tengah masyarakat majemuk. Dengan demikian, penelitian ini menegaskan bahwa pembatasan pernikahan beda agama tidak serta‑merta bertentangan dengan prinsip toleransi. Sebaliknya, ia dapat dipahami sebagai bentuk toleransi berbasis nilai hukum dan agama yang menjamin koeksistensi damai sekaligus menjaga integritas ajaran agama dan harmoni sosial.